Practicing Christian doctrine: an introduction to thinking and living theologically - Jones, Beth Felker (Baker Academic, 2023)
"This introductory theology text helps students articulate basic Christian doctrines, think theologically, and connect Christian thought to their everyday life of faith. Now updated and revised throughout"--